Does patient empowerment matter in building loyalty? - Amrul, A. M. A.; Meenatharisni, S.; Sarker, Moniruzzaman * (Wiley, 2021)
Patient empowerment is becoming an essential tool for improving patient–doctor relationships in the healthcare sector. Past research on empowerment within this sector has focused primarily on hospital staff such as nurses and practitioners, whereas very few studies have focused on patients. Moreover, even less attention has been paid to exploring the effect of patient empowerment on patients' trust in doctors, patient–doctor relationship commitment and patient loyalty. Hence, we investigate the relationships between patient empowerment components (patient education, patient perceived control, doctor support and patient participation), patients' trust in doctors and patient–doctor relationship commitment, which leads to the desired state of patient loyalty. Using hospital-intercept surveys, 234 responses were obtained from patients at a private healthcare facility in Kuala Lumpur, Malaysia. Using partial least-squares structural equation modelling (PLS-SEM) techniques, the results demonstrated that patients who were empowered through education and doctor support were more trusting and that such empowerment also fostered relationship commitment towards their doctor. Patient participation and patients' perceived control did not produce similar outcomes. Consequently, relationship commitment was found to be the dominant predictor in building patient loyalty. This study broadens the dimension of patient empowerment by adding patient education, which is shown to have a positive impact on patient–doctor relationships and to promote patient loyalty. In an increasingly competitive healthcare market where patient loyalty is highly sought after, these findings suggest that empowering patients during healthcare consultation is conducive to the building of long-term relationships between patients and their doctors.